2020
DOI: 10.21608/jssa.2020.80152
|View full text |Cite
|
Sign up to set email alerts
|

Text-World Theory in Nicole Disney’s “Beneath the Cracks”: A Stylistic/Cognitive Analysis

Abstract: This paper is a stylistic/cognitive analysis of a narrative based on Text World Theory (TWT) in an attempt to identify the text worlds, the discourse worlds and the subworlds in the text under analysis. Cognitive Linguistics is an interdisciplinary approach incorporating language and cognitive abilities. Emphasis is on the manner by which humans process language and build mental representations, text-worlds, to reach a thorough comprehension of meaning structures. The short story analyzed is "Beneath the Crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They have concluded their study by suggesting that translators should view translation as a cognitivelinguistic process of text-world construction and presentation, which may promise a more proactive approach to translator training by encouraging translator trainees to pay special attention to the expansion of their knowledge structures (Tian & Wang, 2019). Another study to show the impact of TWT in understanding literary texts has been introduced by Hamed (2020). In her study, Hamed (2020) has tried to prove that context-dependent text world analysis of narratives is useful in rendering participants' senses because TWT explains the process of readers' moving from textual information towards the deep nature of text worlds.…”
Section: Text World Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…They have concluded their study by suggesting that translators should view translation as a cognitivelinguistic process of text-world construction and presentation, which may promise a more proactive approach to translator training by encouraging translator trainees to pay special attention to the expansion of their knowledge structures (Tian & Wang, 2019). Another study to show the impact of TWT in understanding literary texts has been introduced by Hamed (2020). In her study, Hamed (2020) has tried to prove that context-dependent text world analysis of narratives is useful in rendering participants' senses because TWT explains the process of readers' moving from textual information towards the deep nature of text worlds.…”
Section: Text World Theorymentioning
confidence: 99%
“…Another study to show the impact of TWT in understanding literary texts has been introduced by Hamed (2020). In her study, Hamed (2020) has tried to prove that context-dependent text world analysis of narratives is useful in rendering participants' senses because TWT explains the process of readers' moving from textual information towards the deep nature of text worlds. The results have shown that TWT demonstrates the cognitive processes taking place through the process of reading, the process that leads to text interpretation and accessing meaning.…”
Section: Text World Theorymentioning
confidence: 99%